(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
Introduction. Under conditions of total impoverishment of the population, the problem of its social protection is becoming increasingly relevance. Low wages, high utility tariffs, a significant number of beneficiaries, disparities between the minimum and maximum pension are the reasons of social tension in society. An effective system of social protection must ensure a decent standard of living and prevent new social conflicts. The purpose of the article. The purpose of the study is to discuss the theoretical aspects of social protection, the study of the dynamics and interconnection of state social standards in Ukraine and the features of social protection in the Volyn region. In accordance with the set goal, the following research objectives have been identified: to reveal modern problems of social protection in Ukraine; analyze the dynamics of state social standards; to study the features of social protection in the Volyn region. Results. The analysis of the dynamics of state social standards showed their increase in the national currency, but in dollar terms only the minimum wage increased, and the subsistence level decreased, which led to a general trend of decreasing the ratio of the subsistence minimum to the minimum wage. Thus, from 2010 to 2021, the dollar against the hryvnia increased 3.54 times, the subsistence level 2.65 times, and the minimum wage 6.5 times. That is, in dollar terms, there was an increase in the minimum wage from 116 in 2010 to 212 (+ 83.7%) in 2021 and a decrease in the subsistence level from 103 in 2010 to 77 (-25.1%) in 2021. This situation is explained by the outstripping growth of the minimum wage compared to the subsistence level, due to the interest of public authorities in increasing revenues from the single social contribution (22% to the wage fund), and unwillingness to increase social costs tied to the subsistence level. It should be noted a significant decline in state social standards in dollar terms in 2015-2016, in particular the minimum wage decreased by 43% and 23% respectively, and the subsistence level decreased by 49% and 25% respectively, due to significant inflationary processes caused by changes in political situation, the annexation of Crimea and the start of hostilities in the east. Conclusions. Social protection of the population is the main function of the state and requires redistribution of income in order to ensure social harmony. The basis for overcoming poverty in the country should be to increase the share of the middle class in society, only this will have a lasting effect and bring the country out of social crisis. The size of state social standards is a matter of concern, as they are currently the lowest in Europe. This causes a significant amount of social benefits, including subsidies, increases social tensions in society and leads to a significant outflow of labor. Changes to the procedure for providing housing subsidies defined by the Resolution of the Cabinet of Ministers of 14.04.2021 № 420 significantly limited and complicated the procedure for obtaining it, which led to panic among the population, long queues to local departments of social policy and increased public dissatisfaction with the existing pricing system for housing and communal services. In order to improve the well-being of citizens, it is necessary to: form a strategy to overcome poverty in the country; redirect funds from subsidizing the population to increase the minimum wage; to change the principles of pricing for housing and communal services in the direction of their reduction, through structural changes in the gas and electricity market; review the size and procedure for forming the subsistence level; abolish special pensions, ensuring a gap between the minimum and maximum pensions of no more than five times, replace the system of benefits with targeted payments.